Variation in changes in the incidence of colorectal cancer by age and association with screening uptake: an observational study - Annie S Anderson; Callum G Fraser; Judith A Strachan; Robert JC Steele; Gavin RC Clark; Thomas G Godfrey (BMJ Open)
Objectives In developed countries, the incidence of colorectal cancer (CRC) has declined in the over 50 years age group but increased in younger people. We studied CRC incidence by age and the influence of screening uptake.Design Age-standardised and sex-standardised incidences for CRC from 1997 to 2017 were obtained from the Scottish Cancer Registry (SCR). In addition, linkage between the Scottish Bowel Screening Database and the SCR allowed investigation of any association between screening participation and CRC incidence.Setting Scotland and the Scottish Bowel Screening Programme, in which guaiac faecal occult blood test screening was piloted from March 2000 and fully rolled by December 2009.Participants From the introduction of screening in 2000 through to 2017, 2 395 172 were invited to participate, of whom 1 487 999 participated at least once.Main outcome measures Incidence of CRC.Results In the screening age range (50–74 years), CRC incidence peaked at 156.5 cases per 100 000 in 2010 after full roll-out of screening across Scotland but fell to 123.9 per 100 000 in 2017. However, under 50 years, there was a rise from 5.3 cases per 100 000 in 2000 to 6.8 per 100 000 in 2017. When CRC incidence was examined in those who had been offered screening, incidence fell in the participant group more than in the non-participant group after roll-out of screening was complete. Analysis of cumulative incidence demonstrated that CRC incidence in the participant group remained consistently below that of the non-participant from around 7 years of follow-up.Conclusions The incidence of CRC in Scotland has declined in the over 50 years age group but increased in younger people. It is likely that population screening has contributed to the reduction in CRC incidence in the over 50 years age group.